Simulation of the scenario of the biaxial wheel fatigue test. (December 2017) - Santiciolli, Fabio M.; Möller, Riccardo; Krause, Ivo; Dedini, Franco G.
Highlights: The virtualization of the scenario of a fatigue life validation test of wheels. Three software are used to simulate three important aspects of the test scenario. Use of a tire model in a test facility simulation instead of a vehicle simulation. Novel simulation approach to this kind of test considering previous literature. Comparison between the simulated and the acquired data. Abstract: This paper presents a new approach to the virtualization of the scenario of the biaxial wheel fatigue test. This test is the state-of-art and the standard requirement for the validation of vehicle wheels. During this test, tire and wheel specimens run inside an inner drum while standardized vertical and horizontal loads are applied. Thus, the scenario of this test can be modeled in three levels: the multibody dynamics of the test facility, the wheel/tire/inner drum contact, and the analysis of the flexible wheel. In the proposed virtualization, the multibody dynamics of the test facility was implemented in MSC.ADAMS. The wheel/tire/inner drum contact was simulated by means of CDTire; as it works parallel to MSC.ADAMS, one single co-simulation could perform the tire dynamics and the test facility dynamics. Finally, the wheel strains were calculated by an ABAQUS simulation, which received the tire/wheel load data from the simulation in MSC.ADAMS and CDTire. A physical test facility and a physical wheel specimen were instrumented, allowing the comparison between acquired and simulated data. The use of this specialized software is a novelty in the virtualization of the scenario of this test; furthermore a high detailed simulation is required for the further development of such already well established test procedure.